Protective effect of L-carnitine on rhabdomyolysis-induced acute kidney injury via Nrf2/HO-1 activation - ZHANG Yuan-yuan; ZHANG Jian-rong; GENG Yan-qiu; ZHANG Yan-xia (Linchuang shenzangbing zazhi)
Objective To observe the protective effects of L-carnitine on renal function in rhabdomyolysis-induced acute kidney injury(AKI) in rats and the underlying mechanism.Methods Thirty-six adult rats were randomly divided into 3 groups:control group,AKI model group,and L-carnitine treatment group[rhabdomyolysis-induced AKI rats given L-carnitine(200 mg/kg)].50%glycerin was intramuscularlly injected to establish rhabdomyolysis-induced AKI models in rats.Blood samples were taken from the heart from rats and the kidneys were harvested.Serum creatine kinase(CK),blood urea nitrogen(BUN),serum creatinine(SCr) levels were measured,and renal pathological changes were observed under light microscope.RT-PCR and immunohistochemistry were used to detect the expression of Nrf2 and HO-1 in renal tissues.Enzyme linked immunosorbent assay(ELISA) was applied to detect the expression of SOD and MDA in renal tissues.Results As compared with control group,CK,BUN,SCr,Nrf2,HO-1,MDA and ATN were significantly elevated,and SOD was significantly reduced in model group and L-carnitine treatment group(F = 8.78-200.77,q=S.42-19.40,P<0.05).As compared with model group,CK,BUN,SCr,MDA and ATN were significantly decreased,and Nrf2,HO-1 and SOD were significantly elevated in L-carnitine treatment group(q = 4.15-15.39,P<0.05).Conclusions L-carnitine can ameliorate rhabdomyolysis-induced AKI,which may be related with its anti-oxidative stress.